Arabidopsis synaptotagmin 1 mediates lipid transport in a lipid composition‐dependent manner. (13th May 2022) - Qian, Tiantian; Li, Chenlu; Liu, Furong; Xu, Kai; Wan, Chun; Liu, Yinghui; Yu, Haijia
Abstract: The endoplasmic reticulum (ER)‐plasma membrane (PM) contact sites (EPCSs) are structurally conserved in eukaryotes. The Arabidopsis ER‐anchored synaptotagmin 1 (SYT1), enriched in EPCSs, plays a critical role in plant abiotic stress tolerance. It has become clear that SYT1 interacts with PM to mediate ER‐PM connectivity. However, whether SYT1 performs additional functions at EPCSs remains unknown. Here, we report that SYT1 efficiently transfers phospholipids between membranes. The lipid transfer activity of SYT1 is highly dependent on phosphatidylinositol 4, 5‐bisphosphate [PI(4, 5)P2 ], a signal lipid accumulated at the PM under abiotic stress. Mechanically, while SYT1 transfers lipids fundamentally through the synaptotagmin‐like mitochondrial‐lipid‐binding protein (SMP) domain, the efficient lipid transport requires the C2A domain‐mediated membrane tethering. Interestingly, we observed that Ca 2+ could stimulate SYT1‐mediated lipid transport. In addition to PI(4, 5)P2, the Ca 2+ activation requires the phosphatidylserine, another negatively charged lipid on the opposed membrane. Together, our studies identified Arabidopsis SYT1 as a lipid transfer protein at EPCSs and demonstrated that it takes conserved as well as divergent mechanisms with other extend‐synaptotagmins. The critical role of lipid composition and Ca 2+ reveals that SYT1‐mediated lipid transport is highly regulated by signals in response to abiotic stresses. Abstract : Plant SYT1 plays a vital role in maintaining plasma membrane integrity. The molecular mechanisms of SYT1, however, remain less understood. In this work, we demonstrate that Arabidopsis SYT1 is a lipid transfer protein at the endoplasmic reticulum ‐ plasma membrane contact sites. The SYT1‐mediated lipid transport depends on the lipid composition of the opposed membrane. While phosphatidylinositol‐4, 5‐bisphosphate is critical for the lipid transfer activity of SYT1, the Ca 2+ ‐stimulated lipid transport further requires phosphatidylserine, another negatively charged lipid.